Incidence and Clinical Significance of Posterior Glenoid Deficiency in Patients with Posterior Glenohumeral Instability. Issue 7 (30th July 2018) - Elsenbeck, Michael; Wolfe, Jared; Nappo, Kyle E.; Christensen, Daniel; Waltz, Robert A.; LeClere, Lance E.; Dickens, Jonathan F.
Objectives: Posterior glenohumeral instability accounts for 10-40% of instability repairs yet the degree posterior bone deficiency contributing to labral repair failure is unclear. The purpose of this study is to determine the incidence, characteristics, and clinical impact of posterior glenohumeral bone deficiency in patients undergoing posterior shoulder stabilization. Methods: All consecutive patients undergoing isolated soft tissue only posterior labral repairs from 2008-2016 at our institution were identified via review of surgical case logs. Posterior bone deficiency was calculated using the best fit circle method along the inferior 2/3 s of the glenoid by two independent observers. The intra-observer and inter-observe reliability ICC of this method was .96 and .86, respectively. Patients were divided into three groups, no bone loss (0-5%), minimal bone loss (5-13.5%) and moderate posterior bone deficit (>13.5%). Our primary outcome, was reoperation for any reason, secondary outcomes were military separation due to the operative shoulder, and placement on permanent restricted duty due to the operative shoulder. Additional comparisons between the groups were made on the basis of preoperative clinical and radiographic characteristics. Results: We identified 66 patients that met our inclusion and exclusion criteria. Our median follow up time was 22 months (range 7-144months). 39 of the 66 patients had no measureable bone deficiency while 18 patients had between 5 and 13.5%, and 9 patients had greater than 13.5%. The greatest amount of bone deficiency in a patient was 27%. The reoperation rates were 7.7% in the no bone deficiency group, 16% in the minimal bone deficiency group, and 33% in the moderate group, this difference was statistically significant (p=.036). There was no difference in rates of military separation, or restricted duty between groups. Additionally, patients with posterior glenoid bone deficiency, were more likely to complain of instability instead of pain on initial presentation (p=.002), and were more likely to have a positive posterior load shift test (p=.027). Conclusion: Posterior glenoid bone deficiency is common and potentially under recognized in patients undergoing surgery for posterior glenohumeral instability with over one-third of our patients having some degree of bone deficiency. In patients with moderate glenoid bone deficiency (>13.5%), soft tissue only stabilization procedures may have higher reoperation rates then in patients without bone deficiency. On preoperative evaluation the primary complaint of instability instead of pain and a positive posterior load shift were predictive of the presence of posterior glenoid bone deficiency.